RANCANG BANGUN ROBOT SMART FARMING BERBASIS COMPUTER NUMERICAL CONTROL (PENGGERAK X, Y, Z) - Muhamad Rama Ardiansyah; Muhammad Diono (ABEC Indonesia, 2021)
Farming in urban areas by utilizing the yard area or corners of the house efficiently is often referred to as urban farming. The main objective of this project is to create a sophisticated agricultural system with the help of IOT applications, so that it can easily maintain agriculture, this robot which will later be named SF-BOT. SF-BOT has options for planting seeds, measuring soil moisture and watering. To implement this feature, SF-BOT works which is controlled by Computer Numerical Control (CNC) with the help of Arduino and Raspberry pi. Testing of planting and watering seeds at each coordinate point The success rate is said to be almost perfect, with a level of accuracy and precision of the tool of 83%. The Real Time Clock (RTC) test is said to be close to precision with a tool precision level of 85.7. The duration of planting and watering at SF-Bot at point 1 the closest plant coordinate takes 20 seconds for seed A and at point 12 plant coordinates on seed C takes 2 minutes 8 seconds, where point 12 is the farthest coordinate point of planting. Watering time at 12 plant points on SF-Bot takes 2 minutes 30 seconds. Keywords: Computer Numerical Control, Arduino, Raspberry pi, internet of things